Filtrates and sludge generated in the physicochemical treatment of wastewater from the lead-acid batteries production - Rauckyte-Żak, Terese; Gorczyca, Beata; Żak, Sławomir (International Conference “Environmental Engineering”, 2020)
Total lead (TPb) exists in Crude Wastewater (CW) from production of Lead-Acid Batteries (LABs) in water (WPb) and solid phase (SPb) as colloids and suspended solids. Sludges produced in chemical treatment of these wastewater were dewatered in Chamber Pressure Press (CPP). Samples of dewatered sludges (Ss) were analyzed with Toxicological Characteristic Leaching Procedure (TCLP) to determine concentration of Pb in the extract (Ex(TCLP)). Selected sludges were also analyzed using Tessier’s procedure for fractions. Concentration of lead in filtrates (Fs) as well as in the sludges were different, depending on the mechanisms involved in converting soluble lead to its less soluble forms. Sludges produced in chemical treatment with 10% NaOH and Lime Milk (LM), CaO or Ca(OH)2, followed by coagulation with (Ixonos Na3T ®) contained lowest concentration of lead. The TPb in filtrates below 0.4 mg/L at pH > 8.90±0.3, and Ex(TCLP) of less than 5.0 mg/L were obtained in this treatment. Potential recovery of lead from sludges have been investigated.
Keywords: lead-acid batteries production; industrial wastewater treatment; sludge; TCLP leached lead; Pb fractional analysis